THE PLACE OF UZBEK ARCHITECTURE IN WORLD HERITAGE: MONUMENTS INCLUDED IN THE UNESCO LIST - A. R. Abobakirov (Bright Mind Publishing, 2025)
Uzbekistan, located at the heart of Central Asia, has for centuries served as a cultural and architectural crossroads of civilizations, integrating Persian, Turkic, Islamic, and nomadic traditions into a unique architectural language that today forms a cornerstone of world heritage. The cities of Samarkand, Bukhara, Khiva, and Shahrisabz, along with their monumental ensembles and sacred spaces, are recognized by UNESCO for their outstanding universal value, symbolizing the Silk Road’s role in fostering cultural exchange, technological innovation, and spiritual dialogue between East and West. This paper investigates the global significance of Uzbek architecture through a systematic analysis of its UNESCO-listed monuments, drawing upon historical sources, field research, and architectural studies. Employing an IMRaD structure, the study explores the methodological frameworks for evaluating heritage, analyzes the architectural achievements of Timurid, Shaybanid, and Khanate dynasties, and examines the results of heritage preservation and their global implications. Findings demonstrate that Uzbek monuments not only exemplify masterful use of scale, decoration, and urban planning but also function as living testimonies to intercultural dialogue and identity. The discussion addresses challenges of conservation, urbanization, and sustainable tourism, stressing the importance of integrating modern preservation technologies with traditional craftsmanship. Ultimately, this paper concludes that Uzbek architecture occupies a vital place in global heritage, providing a model for how historical continuity, cultural diversity, and artistic brilliance can be preserved while contributing to contemporary international cultural identity.
Keywords: Uzbek Architecture; UNESCO World Heritage; Samarkand; Bukhara; Khiva; Shahrisabz; Silk Road; Architectural Heritage.